Chemokine profile in the serum of patients with leptospirosis - Mariano, Iago H. de Miranda; Blanco, Roberta M.; de Souza, Camila Eulalio; de Freitas, Geovanna Silva; Ho, Paulo Lee; Martins, Elizabeth A. L.; Romero, Eliete C.; da Silva, Josefa B. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionLeptospirosis is a global zoonosis that affects more than one million people per year, with a lethality rate of approximately 15%. Chemokines are crucial in the immune response against Leptospira, recruiting leukocytes to the site of infection and regulating immune activity. In previous studies, we have shown that CCL2, CXCL5, and CCL8 are involved in the leptospirosis process, although the mechanisms are not understood. MethodsIn this study, we present the frequency of Leptospira serovars in human samples. We then evaluated the profile of various chemokines in sera from patients diagnosed with leptospirosis, assessing the possible correlation between them. Moreover, we evaluated the changes in the chemokine profile on different days after the first symptoms. The frequency of the Leptospira serovars in human samples is presented. Results and discussionThe main findings were that CCL5, CXCL5, and CXCL9 are highly expressed during leptospirosis, indicating a special role of these molecules in the immunity and pathogenesis of the disease. The correlation analysis of detected chemokines CXCL11, CXCL9, CCL3, and CCL2 helps to clarify the role of each cytokine in leptospirosis. The possible use of CCL5 as a biomarker for complementary diagnosis of the disease is suggested.